Interaction of Nitrate Assimilation and Photorespiration at Elevated CO2 - Krämer, Konrad; Brock, Judith; Heyer, Arnd G. (Frontiers in Plant Science, 2022)
It has been shown repeatedly that exposure to elevated atmospheric CO2 causes an increased C/N ratio of plant biomass that could result from either increased carbon or – in relation to C acquisition - reduced nitrogen assimilation. Possible reasons for diminished nitrogen assimilation are controversial, but an impact of reduced photorespiration at elevated CO2 has frequently been implied. Using a mutant defective in peroxisomal hydroxy-pyruvate reductase (hpr1-1) that is hampered in photorespiratory turnover, we show that indeed, photorespiration stimulates the glutamine-synthetase 2 (GS) / glutamine-oxoglutarate-aminotransferase (GOGAT) cycle, which channels ammonia into amino acid synthesis. However, mathematical flux simulations demonstrated that nitrate assimilation was not reduced at elevated CO2, pointing to a dilution of nitrogen containing compounds by assimilated carbon at elevated CO2. The massive growth reduction in the hpr1-1 mutant does not appear to result from nitrogen starvation. Model simulations yield evidence for a loss of cellular energy that is consumed in supporting high flux through the GS/GOGAT cycle that results from inefficient removal of photorespiratory intermediates. This causes a futile cycling of glycolate and hydroxy-pyruvate. In addition to that, accumulation of serine and glycine as well as carboxylates in the mutant creates a metabolic imbalance that could contribute to growth reduction.